Emotional sphere of personality: vectors of studying - Kirilenko, T. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
Five vector directions of studying the emotional sphere of personality are singled out: self-creation of emotions and feelings, levels of emotional experience, emotional readiness for changes, emotional self-knowledge, spiritual experience. A threecomponent (horizontal, vertical, through) model of studying emotions and feelings of personality is presented.According to classical ideas, emotional sphere of personality is less studied in comparison with cognitive as it is difficult to empirical research and linked to the deep intimate aspects of human life as a bright personality. Without a holistic view of content and functionality of emotions and feelings, their main areas of study, methods, we lose an opportunity to understand the practice of building well-being of the individual, the direction of personal growth for the organization of psychological support, which is important for each person separately and for variety of group communities.The objective of this article is to identify and organize vectors in studying process of emotional sphere of personality and to present a model for its studying.
Keywords: emotional sphere; self-creation; emotional experience; emotional readiness; emotional self-knowledge; spiritual experience